Small-scale phyco-mitigation of raw urban wastewater integrated with biodiesel production and its utilization for aquaculture. (February 2020) - Arora, Neha; Jaiswal, Krishna Kumar; Kumar, Vinod; Vlaskin, M.S.; Nanda, Manisha; Pruthi, Vikas; Chauhan, PK
Graphical abstract: Highlights: A low-cost small scale (35L), HRAP to efficiently mitigate raw urban wastewater. High nutrient (97%) and organic carbon (74%) removal using Chlorella sorokiniana . High microalgal biomass with enhanced lipid content for biodiesel production. Re-utilization of treated wastewater for sucker fish aquaculture. Abstract: A low-cost small-scale high-rate algal pond (HRAP) was constructed to investigate the synergistic potential of a novel oleaginous microalga, Chlorella sorokiniana for phyco-mitigation, and biodiesel production using raw urban wastewater. An enhanced nutrient removal (97%), total organic carbon (74%), alkalinity (70%) and hardness (75%) from the wastewater was obtained. The microalga dominated in the HRAP as ~90% increase in the dissolved oxygen with high biomass (1.13 g/L) was noted. The microalga biomass showed sufficient lipid content (~31% of dry cell weight) as compared to control (Bold's Basal media). The total lipid profiling of the microalga cultivated in wastewater showed augmentation in the levels of both storage and neutral lipids with good quality fatty acids composition. Moreover, the sucker fishes grew healthy in the treated wastewater with an increase in body weight.